Platelet aggregability in patients with interstitial pneumonias - Handa, Tomohiro; Watanabe, Kizuku; Tanizawa, Kiminobu; Oga, Toru; Aihara, Kensaku; Ikezoe, Kohei; Sokai, Akihiko; Nakatsuka, Yoshinari; Hirai, Toyohiro; Nagai, Sonoko; Chin, Kazuo; Horiuchi, Hisanori; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Recent epidemiological studies have shown that patients with interstitial pneumonia have an increased risk of cardiovascular events. Although the presence of a coagulation/fibrinolysis abnormality in idiopathic pulmonary fibrosis (IPF) has been reported, platelet aggregability has not been evaluated in interstitial pneumonias. This study aimed to investigate platelet aggregability in patients with interstitial pneumonias. Methods: This observational cohort study included 59 patients with interstitial pneumonias [19 with IPF, 23 with other idiopathic interstitial pneumonias (IIPs), and 17 with connective tissue disease-associated interstitial pneumonias (CTD-IPs)] and 23 healthy control subjects. ADP- and collagen-induced platelet aggregability was measured together with coagulation/fibrinolysis markers. Whole blood (WB) and platelet rich plasma platelet aggregation were measured using the screen filtration pressure and optical aggregometer techniques, respectively. The platelet aggregation threshold index (PATI) was calculated; a lower PATI indicated enhanced platelet aggregability. Results: ADP-induced WB-PATI was significantly decreased in CTD-IPs [log WB-PATI median 0.31 (inter-quartile range, 0.07–0.34) μM, n = 17] compared with that in controls [0.35 (0.32–0.45) μM, n = 23] (p < 0.05). However, there was no significant difference in platelet aggregability between the other patient groups and controls. In contrast, d-dimer, thrombin–antithrombin complex, and von Willebrand factor levels were significantly higher in all patient groups compared with those in controls (p < 0.001). Platelet aggregability was not associated with either disease severity or survival. Conclusions: Serum coagulation and fibrinolysis markers significantly increased in IIPs and CTD-IPs. In contrast, platelet aggregability was only weakly enhanced in CTDs, but not in IIPs.